2017
DOI: 10.4149/neo_2017_508
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CFTR enhances sensitivity of prostate cancer cells to cisplatin via inhibition of autophagy

et al.

Abstract: Prostate cancer is one of the most lethal diseases in men worldwide. Although the survival rate of men diagnosed with prostate cancer has increased with the improvement of treatments, drug resistance still remains a big challenge for improving overall survival. Cystic fibrosis transmembrane conductance regulator (CFTR), a cAMP-activated anion channel, has been reported to have a pivotal role in the pathogenesis of various cancers, but its role in chemoresistance of prostate cancer cells is poorly understood. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Loss of functional CFTR expression is thought to disturb the balance between fluid secretion and absorption into the epithelial layer, leading to cystic fibrosis liver disease 9 , 10 . Accordingly, a depressed autophagy has previously been reported in prostate cancer cells due to knockdown of CFTR 11 , 12 . Notably, liver is a major metabolic organ of Hcy, but there is no evidence to show the correlation between CFTR and hepatic autophagy induced by Hcy.…”
Section: Introductionmentioning
confidence: 85%
“…Loss of functional CFTR expression is thought to disturb the balance between fluid secretion and absorption into the epithelial layer, leading to cystic fibrosis liver disease 9 , 10 . Accordingly, a depressed autophagy has previously been reported in prostate cancer cells due to knockdown of CFTR 11 , 12 . Notably, liver is a major metabolic organ of Hcy, but there is no evidence to show the correlation between CFTR and hepatic autophagy induced by Hcy.…”
Section: Introductionmentioning
confidence: 85%
“…That is because some plant extracts trigger the generation of autophagy of cancer cells while suppressing the proliferation [ 7 , 9 ]. Autophagy confers protective effect against toxicity of anti-tumor agents, thus it, to some extent, inhibits apoptosis of cancerous cells and results in chemo-resistance [ 17 ]. Sal has been emerged as an important plant extracts for the treatments of cancer and age-related diseases [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation effect of CFTR on autophagy was also found in prostate cancer. (18) However, relationship between CFTR and mitophagy is rarely reported. Here, we observed CFTR could also activate mitophagy in cardiomyocytes, and de ciency of CFTR might result in worse I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, role of CFTR in other diseases are also reported. It was found inhibition of CFTR might promote prostate cancer sensitivity to cisplatin by inhibition of autophagy (18). Another study also showed CFTR could inhibit epidermal growth factor receptor-dependent proin ammatory chemokine production (19).…”
Section: Introductionmentioning
confidence: 99%